CORRELATION OF ALANINE AMINO TRANSFERASE WITH HEPATITIS B VIRAL LOAD AND HBe ANTIGEN POSITIVITY - shah, Nazir; Mehmood, Nasir; Shah, Mian Mufarih; Khan, Muhammad Zubair (Journal of Postgraduate Medical Institute, 2021)
ABSTRACT Objective: To find out the relationship of alanine amino transferase with viral load and HBe antigen positivity in the HBs Ag positive patients. Methodology: This cross sectional study was performed ON 63 patients in medical unit of Hayatabad Medical Complex Peshawar from October 2018 to August 2019. All HBs Ag positive patients, both male and female, were enrolled from the wards and outpatient department (OPD). Patients with cirrhosis liver, decompensated liver disease, acute hepatitis and other hepatotoxic liver conditions were excluded from the study. Every patient was tested for HBs Ag by enzyme linked immunosorbent assay (ELISA). Serum alanine amino transferase (ALT), quantitative polymerase chain reaction (PCR) for (hepatitis B virus) HBV DNA and HBe Ag from the sample taken at the same time and date. According to the reference range, ALT of 40 U/L was considered the upper limit of normal. A level of two times of the upper limit of normal (ULN) was considered as high. Results: Out of sixty-three patients, 55.55% (n=35) were males and 44.44% (n=28) were females. Patients age range was 15 to 70 (mean=41( ± 17). Out of these patients, 49% (n=31) were having a viral load of 2000 iu/ml or more and 33.33% (n=21) were having HBe Ag positive status. Raised ALT was noted in 39.69% (n=25) patients. No difference was found regarding these parameters in the males or females. About 71 % of the patients with a viral load of more than 2000 iu/ml were having ALT raised by more than two times of the upper limit of normal. The frequency of raised ALT with HBe Ag positive patients was about 85.7% (n=18). Conclusion: Alanine amino transferase does not have a close correlation with the viral load in HBV patients. It is comparatively more correlated with HBe Ag positivity.